Examining the Topics of Master's Theses in Dari Persian Language and Literature at Kabul University - Naziri, Nik Mohammad; Rustamzada, Ataullhaq (Journal of Social Sciences - Kabul University, 2025)
This paper focuses on Analysis the titles of master’s theses in the Persian-Dari Language and Literature program at Kabul University. this paper, in one view, reveals the existing gap in this field and attempts to suggest ways to resolve the issues and prevent their repetition. On the other hand, it seeks to help students and researchers adopt appropriate and standard methods when selecting thesis titles. The findings indicate that most thesis titles have been selected within the field of literary studies, while the fewest belong to linguistics. Major problems found in thesis titles include choosing the research topic instead of the actual title and failure to clearly define and limit the scope of titles, which often results in long and overly broad statements. These are the most prominent deficiencies observed in the collected thesis titles.